The Continuous Kidnapping in Pasong Putik, Quezon City (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Kidnapping is a major problem for many law enforcement agencies. The primary objective isto catch all the people behind this kind of illegal activity and protect the person from any threatto his surroundings; the primary target of a perpetrator is women; according to the PhilippineNational Police Anti-Kidnapping Group, every year, we are expecting a hundred cases ofkidnapping in a different part of the Philippines which is the primary victim are women to askfor some ransom and favor in exchange of the life of a victim.Respondents assessed the impact of continuous kidnapping in Pasong Putik, Quezon City.Severe or long terms stress, trauma, neglect, cause of kidnapping in Pasong Putik, QuezonCity, sleep problems, low mood, high levels of anxiety, and other mental health problems canmake it difficult in daily life, Experiencing panic attacks, depression, and schizophrenia,Having problem with memory, reality thinking confusion and concentration.The discussion demonstrates the impact of continuous kidnapping in Pasong Putik QuezonCity on how to address the problem encountered by the respondent, and here are some waysto promote and practice safety. Avoid posting your personal information or your homeaddress, conduct free legal advice to the victim, Conduct a seminar about kidnapping at leastonce a month, Install more CCTV cameras on every corner of the street, And the last rank isCarry any self-defense weapon at all times, sharp object such as a ball pen or pepper sprayhas regarded as (Very Agree)
Keywords: Criminology